Influence Of Sex On Academic Outcomes: Case Of Students Of The Department Of Science And Technique Of Socio-Educational Activities (STASE/INJEPS/UAC) - EDOH, KOFFI PIERROT; BIGA, MOUSSA (My University, 2019)
The present research relative to the influence of sex on the academic results of the students of Department of Sciences and Techniques of Socio-Educational Activities (STASE/ INJEPS/ UAC) took into account 468 students. Three hundred and fifty-eight (358) of them are male and one hundred and ten (110) are female. They are all regularly registered for the 2015-2016 and 2016-2017 academic years. Data was analysed using Wilcoxon test in the R (3.5.1) statistical analysis software. Results showed that Female students obtained a significantly higher (p <0.05) average marks (13.64 ± 0.72) than male students (13.19 ± 0.98). Based on those results, we can therefore state that female students of the STASE department normally do better than their counterpart male. These results are congruent with previous findings which showed that in higher education entities, women have better results than men.
Keywords: Academic results; Cultures; Gender; Student(s); University